Pregerminative hydration treatments-dehydration for cucumber seeds (Cucumis sativus L.) - Sanchez, Jorge A.; Calvo, Eric; Orta, Ramon; Muñoz, Barbara (Instituto de Ecología, A.C., 1997)
The object of the present paper was to determinate the effects of hydration - dehydration treatments on fresh and storage cucumber seeds (Cucumis sativus L.) of two varieties (Hatuey-1 and Japonés), harversted in Cuba. We tested seven solutions of different substances for partial hydration. For both varieties the priming treatment only with water and one cycle of hydration - dehydration proved to be the best to break the dormancy or to increase the rate of germination in fresh cucumber seeds, but not in storage seeds.